Sesquiterpenes from Xylaria sp., an endophytic fungus associated with Piper aduncum (Piperaceae) - Silva, Geraldo H.; de Oliveira, Camila M. [UNESP]; Teles, Helder L.; Pauletti, Patricia M.; Castro-Gamboa, Ian [UNESP]; Silva, Dulce H. S. [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Young, Maria C. M.; Costa-Neto, Claudio M.; Pfenning, Ludwig H.; Berlinck, Roberto G. S.; Araujo, Angela R. [UNESP] (Elsevier B.V., 2010)
Two new presilphiperfolane sesquiterpenes, 1 and 2, were isolated from the ethyl acetate extract of Xylaria sp., obtained from the leaves of Piper aduncum, along with two known eremophilane sesquiterpenes, phaseolinone (3) and phomenone (4). Chemical structures of 1 and 2 were established by analysis of spectroscopic data. The four compounds were tested in vitro for antifungal and cytotoxicity activities using CHO (Chinese hamster ovary). Compounds 1 and 2 did not show any antifungal and cytotoxic activity. Compounds 3 and 4 displayed moderate cytotoxic activities, as well as 4 antifungal activity. (C) 2010 Phytochemical Society of Europe. Published by Elsevier B. V. All rights reserved.
Keywords: Xylaria sp.; Piper aduncum; Sesquiterpenes; Endophytic fungus